2021
DOI: 10.1071/rd21153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate COVID-19 infection on semen oxidative status and parameters 14 and 120 days after diagnosis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus causing coronavirus disease 2019 . Because COVID-19 is a multisystem infection, there are some concerns regarding its possible effects on male fertility. This study aimed to investigate the effects of COVID-19 on semen oxidative status and parameters 14 and 120 days after diagnosis in patients presenting with moderate infection (defined as respiratory symptoms, with or without fever, with S p O 2 ,93% and .90% and lung involvement ,50%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…This later work suggests that in severe COVID-19, there is a higher risk to developing DNA oxidative damage, perhaps in part due to sustained oxygen supplementation during in-hospital patient care. Likewise, a study aimed in determining DNA fragmentation in sperm cells, and semen quality of patients with mild cases of COVID-19, found that DNA fragmentation in the sperm cells and oxidative stress markers were higher at 14 days after diagnosis, compared with levels in the same patients 120 days after diagnosis [ 90 , 91 ]. However, as in the previous studies, this work lacked a control group of non-infected subjects.…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…This later work suggests that in severe COVID-19, there is a higher risk to developing DNA oxidative damage, perhaps in part due to sustained oxygen supplementation during in-hospital patient care. Likewise, a study aimed in determining DNA fragmentation in sperm cells, and semen quality of patients with mild cases of COVID-19, found that DNA fragmentation in the sperm cells and oxidative stress markers were higher at 14 days after diagnosis, compared with levels in the same patients 120 days after diagnosis [ 90 , 91 ]. However, as in the previous studies, this work lacked a control group of non-infected subjects.…”
Section: Potential Indirect Mechanisms Of Sars-cov-2 Induced Dna Damage: Aberrant Inflammation Immune Response and Oxidative Damagementioning
confidence: 99%
“…Clinical studies report that SARS-CoV2 infection increases the concentration of ROS, together with Antioxidants 2021, 10, 1283 2 of 20 malondialdehyde (MDA). Moreover, such a virus seems to reduce the percentage of motile spermatozoan, impairing both motility and morphology [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…20 These data, suggesting oxidative stress is a significant contributor to the compromised semen quality seen in patients following COVID-19 infection, have been supported in independent studies. 21 However a causative link between oxidative stress and the decline in semen quality observed following COVID-19 infection has yet to be formally demonstrated.…”
mentioning
confidence: 99%